Religion and mental health among older adults in Thailand: a national survey study - Klangrit, Suriya; Perrodin, David D.; Siripaprapakon, Yasotara; Choudhry, Fahad Riaz; Intaranggkul, Thittayawadee; Pratoomkaew, Suthat; Khemsiri, Khunthong; Saengrung, Kan; Vachirayano, Watchara (Emerald Group Publishing Ltd, 2021)
Purpose–This study aims to investigate the association between mental health and religion amongThailand’s elderly population. The role of religion and culture remains limited despite the significantnumber of devout followers of religions in Thailand. Thai cultural and religious contexts have a dominantand persuasive influence on the lives of Thai older adults.